Whole genome sequence of SARS-COV-2 from Covid-19 acquired hemophilia patient - Zainulabid, Ummu Afeera; Aslam, Ayesha; Hussain, Mushtaq; Ibrahim, Ismail; Periyasamy, Petrick; Kamarudin, Norhidayah; Ahmad, Hajar Fauzan (Elsevier, 2023)
Acquired hemophilia is an atypical pathology of SARS-CoV-2 infection, which could be variant associated. Here, we share a sequence of the SARS-CoV-2 genome from patient with COVID-19 acquired haemophilia. We explore its lineage, genomic and novel structural variations.